Ocupação pré-histórica do litoral norte gaúcho : um olhar sobre o invisível - Pereira, Gilson Laone (2013)
The proposal of this paper is to present direct data of paleosols of two sambaquis, Marambaia I e Figueira II located in the North Shore of Rio Grande do Sul. This research had it´s origin from an attempt to explore the sediment of these sites because they were different from the other ones within the constructive process that were verfified in those profiles. Samples of these sediments were taken to the laboratory submitted a fractionated subdivised and taken af to an oven with a temperature of 60°C during 24 hours. After this process these samples were sleved, processed and taken to a microscope. By using this methodology it was approach possible to visualize the micro particles and to supply information about the physical composition of such sediments. The results have shown phytoliths of grasses, sedges, pollen grains and also charred particles. As this paper's main objective was to fallow the visualization promote of micro structures, showing a part of that environment during the occupation, one can say that paper has achieved its goal. In the samples collected at Site Figueira II fungal spores were found. This kind of fungus because of this "obligatory symbiosis " need the presence of exudates root to emit hyphae, but it only occurs in dry environments. Places constantly affected by floods inhibit its development. The presence of these fungal spores suggests the occurrence of wet ground soils but not soaked. This information leads us to understand that the environment is getting stable where the Restinga starts to expand by about Holocenic cords. The presence of charred vegetable tissues were limited and may not be interpreted as being remains of campfire or daily human, but the increase these carbonized (charred) particles can indicate, the action of burned of origin anthropic.